1986
DOI: 10.1111/j.1399-0039.1986.tb01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine MHC‐class II antigens on B and T lymphocytes1

Abstract: The Nethe-lands MHC-class I1 antigens on canine lymphoid cells were detected with monoclonal antibodies (Mabs). On the basis of reactivity with resting or activated T lymphocytes two groups of Mabs were reported earlier. Non-activated T lymphocytes expressed MHC-class I1 antigens recognized by the first group whereas the second group recognized only MHC-class I1 antigens on activated T lymphocytes. In this study we analysed the reactivity pattern of both groups of Mabs with purified canine B lymphocytes. One-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…This value was superior to the diagnostic reliability previously reported for other methodologies for diagnosing HS in dogs . MHC class IIα was expressed in particular leukocytes, including lymphoid cells, DCs, macrophages, and other antigen‐presenting cells . The present results showed that MHC class IIα mRNA expression was comparatively higher in HS cells than in other cells originating from leukocytes, including inflammatory and lymphomatous cells.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…This value was superior to the diagnostic reliability previously reported for other methodologies for diagnosing HS in dogs . MHC class IIα was expressed in particular leukocytes, including lymphoid cells, DCs, macrophages, and other antigen‐presenting cells . The present results showed that MHC class IIα mRNA expression was comparatively higher in HS cells than in other cells originating from leukocytes, including inflammatory and lymphomatous cells.…”
Section: Discussioncontrasting
confidence: 73%
“…MHC class IIα, CD11b, and CD11c are expressed to some extent in tissues and organs of normal dogs, as well as on antigen‐presenting cells such as DCs and macrophages . We experimentally determined the mRNA expression levels of these SAs in several organs of normal dogs, including the bladder, bone marrow, gastrointestinal tract, heart, kidney, liver, lung, lymph nodes, muscle, pancreas, spleen, and subcutaneous tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If class I1 antigens are normally expressed on a majority of equine peripheral blood lymphocytes, as is the case in dogs (Doveren et al 1986), this would make serological detection of class I1 antigens possible on unseparated PBL. At the same time, these results may reflect a variability in the expression of class I1 antigens on peripheral blood cells in the horse causing these apparently conflicting reports and also reflected in the technical difficulties encountered by laboratories during the workshop.…”
Section: Fifh International Ela Workhop 453mentioning
confidence: 99%
“…In cattle and horses, activated T cells were observed to express class II on their cell surface [27,28]. MHC class II canine expression has been found on both naïve as well as activated T cells [29]. Activated rat T cells have been reported to express MHC class II molecules [30,31].…”
Section: Introductionmentioning
confidence: 97%